Late-18th- and Early-19th-Century Inuit and Europeans in Southern Labrador - Auger, Réginald (ARCTIC, 1993)
The Inuit presence, except at Red Bay, is not archaeologically visible until the end of the 18th century, despite the written accounts that document their presence in the Strait of Belle Isle from as early as the 16th century. It appears that they were attracted by the increased European fishing activities in the area. The European presence consisted of fishermen (planter fishermen) posted at the best fishing locations in the Strait of Belle Isle. They adopted a housing style borrowed from the Labrador Inuit, and that trait is notable for the period between the last decade of the 18th century into the middle of the 19th century. The similarities observed between the two ethnic groups demonstrate how complex it is to differentiate them, as a result of cross-acculturation. The Inuit living in close proximity to European stations replaced their traditional material culture with European-made goods in a very short time period, while the European settlers were building sod houses identical to what we know of the 19th-century Labrador Inuit.Key words: Strait of Belle Isle, Labrador Inuit, Europeans, acculturation, historical archaeology, sod houses, 18th-19th century Contrairement à ce que nous apprenons des sources écrites qui nous suggèrent que les Inuit du Labrador fréquentaient le détroit de Belle Isle à une période aussi ancienne que le 16ième siècle, les résultats de recherches archéologiques démontrent qu'à l'exception des restes trouvés à Red Bay, leur présence n'est attestée qu'à la fin du 18ième siècle. Il appert que leur présence aurait découlé d'une attraction accrue suscitée par les activités de pêche des Européens. La présence européenne est attribuée à des groupes de pêcheurs stationnés aux lieux de pêche les plus productifs du détroit. Ces pêcheurs (planter fishermen) dont les évidences sont identifiés entre la dernière décennie du 18ième siècle jusqu'au milieu du 19ième siècle ont adopté un style d'habitation emprunté aux Inuit du Labrador. Les emprunts culturels observés entre ces deux groupes ...